Individualism and working hours: Macro-level evidence - Tatlıyer, ?Mevlüt; Gür, Nurullah (Springer, 2022)
The individualism-collectivism dimension has established itself in interdisciplinary cross-cultural studies in recent decades as the most significant determinant for a variety of economic and institutional outcomes. Individualist societies are characterized by independent selves and loose social ties, and collectivist societies are typified by interdependent selves and strong social ties. In this article, we argue that employees in individualist (collectivist) societies tend to work less (more) since they tend to prioritize themselves and their families over their firms (vice versa), and employers can force employees less (more) and have a harder (easier) time forming a work environment in which long working hours prevail. Using a cross-country empirical analysis, we find that individualism is negatively and significantly associated with working hours. To address endogeneity problems, we use instrumental variables for individualism. Our results are robust to controlling for various relevant variables, employing different estimation techniques, and using different sample sizes.
Keywords: Collectivism; Culture; Individualism; Overworking; Values; Working Hours